Penerimaan kesaksian rukyatul hilal menurut empat mazhab relevansinya dengan keputusan Direktur Peradilan Agama Mahkamah Agung RI - M.Saifulloh; Khairul Anaam; Arofatul Muawanah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
The practice of observing the new moon influences people’s thinking when forming their opinions, leading to disagreements between scholars and astronomers. Some prefer hisab, whilst others rely on rukyat. But all of these are gifts from Allah bestowed upon humanity so that people may think and learn what is true and correct. Both hisab and rukyat share common ground in that the objects used are the moon, the sun, and the earth. Studies reveal several fiqh analyses based on the opinions of scholars from the four schools of thought: Imam Hanafi, Imam Maliki, Imam Shafi’i, and Imam Hanbali. All four have legal opinions regarding the method of accepting testimony of the crescent moon sighting and astronomical calculation in determining the start of the month. Subsequently, in Indonesia, the Neo-Mabims criteria are recognised, implemented by the Ministry of Religious Affairs of the Republic of Indonesia, which then regulates the procedures for the isbat session regarding the testimony of the crescent moon sighting, adapting to contemporary developments. This paper is accompanied by an analysis of the hadith, supplemented by the opinions of the four schools of thought based on these two methods. In those times, only the sighting of the crescent moon was used, and it explains why that era did not employ astronomical calculations, along with the underlying reasons; in the final conclusion, it outlines the differences and methods of accepting testimony from the entirety of the content and presents an analysis based on the authors own perspective.